Causes Of Low Epi Coverage In The Osudoku Sub-District Of The Dangme West District In The Greater Accra Region of Ghana - Opoku-Amankwaah, C. (University of Ghana, 1999)
The Osudoku subditrict has been blamed for the persistent inability of the Dangme West District Health Authority to achieve its immunisation coverage objective. The study objective was to ascertain the accuracy of this assertion of the DHMT and then find the factors causing the alleged poor performance of the subdistrict, if confirmed by the study. Two immunisation coverage surveys using the WHO/ EPI ‘30 cluster sample’ methodology were conducted, one each in the Osudoku and Prampram subdistricts. The Prampram subdistrict is noted by the DHMT to be performing favourably in childhood immunisation. The results of the surveys showed that the Osudoku subdistrict compared favourably with the Prampram subdistrict. Notwithstanding the observed favourable performance in the study some factors were identified which could explain the apparent poor performance of the Osudoku subdistrict. These were:1. The exaggeration of the target population estimates being used by the subdistrict to calculate its childhood immunisation coverage. 2. The reduction in size of the numerator (ie. the 0 - 11 month old children) the subdistrict is supposed to immunise in a given year. 3. Poor data management (MIS) by the MCH staff. Other minor, but equally important factors identified in the coverage survey that could contribute to the apparent low EPI coverage in the Osudoku subdistrict were: 1. Missed opportunities 2. Drop - outs 3. Poor- timing for administering the vaccines.
Thesis (MPH)-University of Ghana